2022
DOI: 10.3389/fphar.2022.1057229
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy for osteoarthritis therapy: Inhibition of glycolysis

Abstract: Osteoarthritis (OA) is a common degenerative disease of the joints. It is primarily caused by age, obesity, mechanical damage, genetics, and other factors, leading to cartilage degradation, synovial inflammation, and subchondral sclerosis with osteophyte formation. Many recent studies have reported that glycolysis disorders are related lead to OA. There is a close relationship between glycolysis and OA. Because of their hypoxic environment, chondrocytes are highly dependent on glycolysis, their primary energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 117 publications
0
18
0
Order By: Relevance
“…However, there are few reports on using serum PKM2 as a biomarker for disease diagnosis. [27][28][29][30] In this study, multivariate regression analysis showed that PKM2 and PCT were independent risk factors for sepsis in ICU patients; the ROC curve analysis showed that the AUC of PKM2 in diagnosing sepsis alone was 0.9154, with a high diagnostic value. Given the limitations of a single indicator, we combined PKM2 with PCT for the diagnosis of sepsis, achieving the highest clinical diagnostic value.…”
Section: Discussionmentioning
confidence: 52%
“…However, there are few reports on using serum PKM2 as a biomarker for disease diagnosis. [27][28][29][30] In this study, multivariate regression analysis showed that PKM2 and PCT were independent risk factors for sepsis in ICU patients; the ROC curve analysis showed that the AUC of PKM2 in diagnosing sepsis alone was 0.9154, with a high diagnostic value. Given the limitations of a single indicator, we combined PKM2 with PCT for the diagnosis of sepsis, achieving the highest clinical diagnostic value.…”
Section: Discussionmentioning
confidence: 52%
“…Studies have shown that under physiological conditions, most cells typically metabolize products through oxidative phosphorylation, but under pathological conditions, injured cells undergo a metabolic reprogramming changing from oxidative phosphorylation to aerobic glycolysis (Xie et al, 2022). Studies have shown that glycolysis plays an essential regulatory role in inflammatory diseases such as sepsis (Corcoran & O'Neill, 2016) and osteoarthritis (Arra et al, 2020; Tan et al, 2022). Our early research also found that valve calcification is accompanied by a high concentration of lipid and glycolysis metabolites (Wang, Huang, et al, 2021; Xie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the production of lactic acid significantly prevents this process. Recent studies have shown that, in addition to metabolic functions, the protein PTM function of lactic acid, that is, lactylation, is an important way for lactic acid to exert cellular functions such as regulating inflammation (Pan et al, 2022; Tan et al, 2022; Wang, Wang, et al, 2022; Wang, Yang, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, ruminal fermentative disorders lead to the excessive accumulation of D-lactate, disrupting normal metabolic processes and causing pathological effects such as polysynovitis [ 1 , 5 ]. The presence of lactate within the joint during arthritis progression is considered a pivotal indicator linked to the inflammatory cascade, currently emerging as a promising target for the advancement of novel therapeutic interventions [ 3 , 41 , 42 ]. Lactate induces the release of Neutrophil Extracellular Traps (NETs) [ 43 ] and activates the secretion of pro-inflammatory cytokines in FLS [ 15 , 17 ], thereby contributing to the inflammation observed in arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of the PI3K/Akt, NF-κB, and HIF-1α pathways may be intricately linked to the potential restoration of glycolytic reprogramming in FLSs [ 46 , 64 ]. Addressing both the inflammatory cascade and metabolic changes during arthritis represents an emerging scientific approach to alleviate joint inflammation [ 41 , 42 ]. Andrographolide, by modulating diverse cellular pathways such as PI3K/Akt, NF-κB, and HIF-1 [ 29 , 65 , 66 ], could exhibit an enhanced anti-inflammatory efficacy due to its multitarget effects on cellular metabolism [ 67 ].…”
Section: Discussionmentioning
confidence: 99%